Sociodemographic Correlates of Human Papillomavirus Vaccine Uptake: Opportunistic and Catch-Up Vaccination in Norway - Dong, Li (Cancers (Basel), 2021)
SIMPLE SUMMARY: HPV vaccination protects against virus that may cause cervical cancer. Opportunistic HPV vaccination (i.e., vaccination at a citizens’ own initiative and cost) has been available in Norway since the first HPV vaccine was licensed in 2006. A routine HPV vaccination program targeting 12-year-old girls was introduced in 2009. A delayed catch-up vaccination program was initiated in 2016, offering HPV vaccination free-of-charge to women born in 1991 and later who had not previously been vaccinated in the routine program. The aim of this study was to assess sociodemographic correlates of opportunistic and catch-up HPV vaccine uptake among women in Norway. We found inequalities in both self-paid opportunistic and free-of-charge catch-up HPV vaccine uptake among adolescents and adult women, with particularly low uptake among women with two immigrant parents and among women with a low household income. ABSTRACT: Achieving equity in human papillomavirus (HPV) vaccination has high priority. In this nationwide registry-based study, we aimed to investigate sociodemographic correlates of HPV vaccine uptake among women who were vaccinated opportunistically at their own initiative and cost during October 2006–June 2018, and among women who were vaccinated free-of-charge in a catch-up vaccination program during November 2016–June 2018. For 840,328 female residents born in Norway between 1975 and 1996, we retrieved HPV vaccination and sociodemographic data from national registries. We used separate models to analyze the sociodemographic correlates of the initiation and completion of HPV vaccination in opportunistic and catch-up vaccination settings. Overall initiation rate for opportunistic HPV vaccination was 2.2%. Uptake increased consistently with birth year, maternal education level, and household income. Having two immigrant parents or a mother working in a lower prestige occupation was strongly associated with low opportunistic vaccination uptake. Similar but weaker inequities were observed in catch-up HPV vaccination. Initiation rate during the first 20 months of the catch-up program was 46.2%. Completion rate was 72.1% and 73.0% for opportunistic or catch-up vaccination, respectively, with small inequities. In conclusion, HPV vaccine uptake was strongly associated with sociodemographic background both in opportunistic and catch-up vaccination settings, with particularly low uptake associated with having two immigrant parents and low household income.